Use of line laser scanning thermography for the defect detection and evaluation of composite material - Li Yin; Song Yuan-jia; Yang Zheng-wei; Xie Xing-yu (Science and Engineering of Composite Materials, 2022)
The line laser scanning thermography was applied for the defect detection and evaluation of composite material in this work, which was carried out by the following procedures. First, a novel contrast enhancement method by homomorphic technology was proposed and validated by a case study. Then, a specimen containing 12 prefabricated defects was detected using line laser scanning thermography and the obtained thermal image sequence and changeable temperature were analyzed. Finally, the defect area was obtained via such thermal image processing as contrast enhancement based on the proposed method, threshold segmentation and quantitative evaluation. The obtained results show that the composite material defects with a depth of less than 4 mm can be detected using line laser scanning thermography but that with a depth of less than 3 mm can be evaluated quantitatively with a small error less than 10%.